2018
DOI: 10.3390/molecules23123221
|View full text |Cite
|
Sign up to set email alerts
|

(−)-Epigallocatechin-3-Gallate (EGCG) Enhances Osteogenic Differentiation of Human Bone Marrow Mesenchymal Stem Cells

Abstract: Osteoporosis is the second most-prevalent epidemiologic disease in the aging population worldwide. Cross-sectional and retrospective evidence indicates that tea consumption can mitigate bone loss and reduce risk of osteoporotic fractures. Tea polyphenols enhance osteoblastogenesis and suppress osteoclastogenesis in vitro. Previously, we showed that (−)-epigallocatechin-3-gallate (EGCG), one of the green tea polyphenols, increased osteogenic differentiation of murine bone marrow mesenchymal stem cells (BMSCs) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
58
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 54 publications
(60 reference statements)
1
58
0
3
Order By: Relevance
“…EGCG, one of the most bioactive catechins derived from green tea, can stimulate bone formation both in vitro and in vivo [17,19,20,31]. The effects of EGCG on the promotion of the fracture healing process, however, remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…EGCG, one of the most bioactive catechins derived from green tea, can stimulate bone formation both in vitro and in vivo [17,19,20,31]. The effects of EGCG on the promotion of the fracture healing process, however, remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The healing process of fractured bone is regulated by the differentiation of osteoblasts and BMSCs. In our previous study, we indicated that EGCG can facilitate the osteogenic differentiation of murine and human BMSCs especially at 10 µmol/L [17]. At the same concentration, EGCG can also decrease osteoclastogenesis via the regulation of osteoprotegrin (OPG) and the receptor activator of Nuclear factor-kB (RANK) ligand (RANKL) in pre-osteoclast feeder cells, ST2 [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the staining solution being discarded, cells were then rinsed in deionized water three times and photographed under the inverted microscope. The amount of calcium mineral deposits was determined by dissolving cell-bound alizarin red staining (ARS) in 10% acetic acid and the absorbance at 540 nm was measured by an ELISA reader (Bio-tek) [19][20][21]. ARS intensity relative to the control treatment was calculated after normalization to the total protein content.…”
mentioning
confidence: 99%